Faktor Yang Mempengaruhi Keputusan Partisipasi Pemilu Dengan Metode TOPSIS - S Sefrika (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Citizen participation in general elections has different trends every year. February 2024 Indonesia will hold presidential and legislative elections. The research aims to investigate the factors that influence general election participation in Indonesia. The research population was 189 citizens who had the right to vote. The research uses the TOPSIS method. (Technique For Others Reference by Similarity to Ideal Solution) is a method used to calculate several alternative criteria offered. The research obtained results of a value of 0.89 for C1, and a value of 0.83 for C4, a value of 0.44 for C2 and a value of 0.32 for C3. The results of this analysis show that the factors influencing active participation in general elections are sociological aspects, followed by economic aspects, political and geographical awareness.